KAJIAN TENTANG PERAN PENTING BASIS DATA BAGI PERPUSTAKAAN - Ahmad Alvin Adriansyah; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
A database is an important part of an information system, because it acts as a foundation for providing information to its users. The implementation of a database in an information system is usually called a database system. This database system is an information system that brings together a combination of several data that are related to each other and makes it available in several diverse applications within one organization Database systems are used to store, manage and process data with the aim of providing efficient, safe and systematic access to information. The goals of a database system include providing flexible access, ensuring data integrity, protecting data from damage and unauthorized access, and enabling shared use. This includes aspects of data connectivity, minimizing redundant data, eliminating dependencies on specific applications, standardizing data element boundaries, and improving the performance of information systems personnel.Modern organizations realize that managing data well and correctly is a successful step in achieving organizational targets. Therefore, many organizations use modern data management with software media. In a system that involves data management, if the system is integrated with software for data management, then of course the system uses Software Data Management concepts.Libraries as one of the providers of information facilities in society certainly require ensuring convenience in every activity that occurs in them. To realize effectiveness in carrying out the functions of a library organization, the role of a database is needed to facilitate data management and access services to the public.